2013
DOI: 10.1111/ffe.12125
|View full text |Cite
|
Sign up to set email alerts
|

Stepped‐isothermal fatigue analysis of engine piston

Abstract: A B S T R A C T Stepped-isothermal fatigue failure is the main failure mechanism of modern engine pistons under bench reliability test condition. This paper presents a methodology for stepped-isothermal fatigue analysis of engine pistons, which consists of a fatigue criterion, evaluation of temperature and stress distribution by finite element analysis and the final life prediction. The major character of the methodology is the fatigue definition of engine pistons with respect to engine load change cycle and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…The generated oxidation on the counterface can act as solid lubricant film or peeling-off layer, depending on the magnitude of sliding distance and normal load [20]. Generally, in actual operating conditions for many components, such as engine pistons, applied load and sliding velocity significantly vary during the operating cycle [24].…”
Section: Introductionmentioning
confidence: 99%
“…The generated oxidation on the counterface can act as solid lubricant film or peeling-off layer, depending on the magnitude of sliding distance and normal load [20]. Generally, in actual operating conditions for many components, such as engine pistons, applied load and sliding velocity significantly vary during the operating cycle [24].…”
Section: Introductionmentioning
confidence: 99%
“…The positive influence of lowering the SDAS on fatigue lifetime has also been reported in high cycle fatigue of other cast materials. [24,25] Particularly, Zhang et al found that the fatigue life varied slightly with SDAS when it was below 30 μm, but dropped quickly with the SDAS increasing above 30 μm, especially at low strain ranges. [24] In this study, the average SDAS of alloy 1.4826 was just below 30 μm, while the average SDAS of alloys 1W6C4N and 3C2N was above 30 μm.…”
Section: The Relationship Between Microstructure and Lcf Behaviormentioning
confidence: 99%
“…[24,25] Particularly, Zhang et al found that the fatigue life varied slightly with SDAS when it was below 30 μm, but dropped quickly with the SDAS increasing above 30 μm, especially at low strain ranges. [24] In this study, the average SDAS of alloy 1.4826 was just below 30 μm, while the average SDAS of alloys 1W6C4N and 3C2N was above 30 μm. Comparing the LCF lifetime and the SDAS in the three investigated alloys, it is suggested that the critical SDAS for affecting LCF lifetime at the low strain range was also around 30 μm in austenitic cast steels.…”
Section: The Relationship Between Microstructure and Lcf Behaviormentioning
confidence: 99%
“…10 This has necessitated intensive research and development of new piston designs and materials that can withstand the increasingly harsh combination of thermo-mechanical fatigue and highcycle fatigue loads. 2, [10][11][12][13][14] Recent investigations are looking at increasing the performance of piston alloys by further increasing the Cu and Ni contents and increasing the Si level above the eutectic although there are concerns about reductions in castability. 5 The aim of these developments has been to achieve maximum performance at high temperatures of 350 °C and above.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a steady increase in engine performance accompanied with requirements for increased system efficiency, minimum weight and more stringent emission legislation . This has necessitated intensive research and development of new piston designs and materials that can withstand the increasingly harsh combination of thermo‐mechanical fatigue and high‐cycle fatigue loads . Recent investigations are looking at increasing the performance of piston alloys by further increasing the Cu and Ni contents and increasing the Si level above the eutectic although there are concerns about reductions in castability .…”
Section: Introductionmentioning
confidence: 99%